Pengaruh Harga Diskon, Citra Merek, dan Kualitas Produk Terhadap Impulse Buying Pembelian Di Shopee - Hendra Cipta; Lia Wdiyawati; Iwang Suwangsih (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2021)
The purpose of this study was to determine the effect of discount prices, brand image and product quality on impulse buying, which is an unplanned purchase action. The population of this research is the 7th semester students of STIE Mahardhika Surabaya who have made purchases at Shopee as many as 902, while the number of samples is 90 respondents. The results of this study are that there is an effect of discount prices on impulse buying, but there is no influence of brand image on impulse buying, as well as no effect of product quality on impulse buying partially. Meanwhile, there is a simultaneous correlation between the X variable and the Y variable.